Kidney dysfunction in chronic heart failure - Khusainova Munira Alisherovna; Kobilova Nigina Akmalovna; Djabbarova Nafisa Mamasoliyevna (Zien Journals, 2022)
Despite the achievements of modern cardiology, chronic heart failure (CHF) is still a prognostically unfavorable condition. Mortality among patients with CHF is 4-8 times higher than in the general population, half of all patients die within 5 years after diagnosis. In patients with CHF of functional class IV (FC), mortality within six months reaches 44%. The association of FC CHF with patient survival is recognized by almost all researchers. It seems obvious that the higher the HCN FC, the worse the prognosis. However, the linear relationship between CHF FC and the mortality of patients is not always traced. The results of a comparative study of the survival of patients with coronary heart disease (CHD) and symptoms of decompensation and without signs of CHF (n=1964), conducted showed that only the terminal stages (IV FC) of CHF play the role of an independent predictor of a poor prognosis (80% of mortality within 3 years), while with I-III FC survival rates are approximately the same: mortality is 38-42%. The immediate cause of decompensation of CHF may be various conditions that by themselves usually do not lead to CHF. Heart and kidney lesions are widespread in the population and often coexist, increasing mortality and the risk of complications. The development of renal dysfunction (DP) is one of the most common comorbid conditions with CHF. A decrease in the contractility of the myocardium leads to a deterioration in the functional state of the kidneys, which, in turn, can cause the progression of CHF. A number of retrospective studies have established a link between the course of CHF and DP, which is accompanied by a deterioration in the prognosis of patient survival. It is believed that the presence of DP in patients with CHF may be a predictor of an unfavorable clinical outcome. However, the degree of DP is not indicated in the diagnosis and its correction is not carried out
Keywords: chronic heart failure; glomerular filtration rate; chronic kidney disease